2018
DOI: 10.1371/journal.pone.0198889
|View full text |Cite
|
Sign up to set email alerts
|

Effect of adiposity on tissue-specific adiponectin secretion

Abstract: Circulating adiponectin levels are lower in individuals with increased BMI and central adiposity. However, they are paradoxically higher in those with peripheral adiposity. We hypothesized that adiponectin secretion from central and peripheral adipose tissue depots may be associated with adiposity levels and its distribution. A total of 55 subjects (69% women) undergoing elective abdominal surgery (mean age: 53 ± 13 years) were recruited. Health history, anthropometrics, and cardiovascular disease risk factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 41 publications
2
33
0
2
Order By: Relevance
“…Our adipocytes, which have matured but not accumulated large lipid droplets, were used 10 days after the initiation of differentiation, a time frame closer to that of Ezure and Amano's small adipocytes (8 days of induction). Interestingly, these small adipocytes secreted more adiponectin than enlarged adipocytes 78 . In addition, Ezure and Amano, in an earlier study, found that exogenous adiponectin increased dermal fibroblast production of type I collagen in a concentration-dependent manner, but without a change in COLA1A gene expression 79 .…”
Section: Discussionmentioning
confidence: 93%
“…Our adipocytes, which have matured but not accumulated large lipid droplets, were used 10 days after the initiation of differentiation, a time frame closer to that of Ezure and Amano's small adipocytes (8 days of induction). Interestingly, these small adipocytes secreted more adiponectin than enlarged adipocytes 78 . In addition, Ezure and Amano, in an earlier study, found that exogenous adiponectin increased dermal fibroblast production of type I collagen in a concentration-dependent manner, but without a change in COLA1A gene expression 79 .…”
Section: Discussionmentioning
confidence: 93%
“…Finally, adiponectin is one of many biochemical variables related with pro- and anti-inflammatory processes that are produced by adipocytes, and it is not produced equally in all adipose tissues. Furthermore, fat distribution can also interfere in the association of adiponectin with cardio-metabolic outcomes [42, 43].…”
Section: Discussionmentioning
confidence: 99%
“…There are data suggesting that adiponectin secretion may differ according to adiposity levels and its distribution. In case of visceral adipose tissue, adiponectin levels decrease with the increase in adiposity, while in subcutaneous adipose tissue, the secretion of adiponectin remains unchanged, especially in women [ 25 ]. In this study the type of adipose tissue was not specified.…”
Section: Discussionmentioning
confidence: 99%